The effect of using the critical thinking strategy in learning the skill Handspring on the floor exercises for student’s college of Physical Education and Sports Sciences - أكرم أكبر رؤى; داود رافد علي; سكران حمزة جمال (Journal of Sport Science Technology and Physical Activities, 2026)
his study aims to investigate the impact of utilizing a critical thinking strategy on the acquisition of the front handspring skill on the floor exercise. To achieve this, the researchers employed an experimental approach featuring a two-equivalent-groups design. The research sample comprised 20 students selected through random sampling. Data were gathered using specialized skill-based assessments. Following the statistical treatment of the data, the findings revealed that the implementation of the proposed strategy had a significant and effective impact on enhancing both the performance and learning outcomes of the front handspring skill. Consequently, the study recommends the integration of this strategy into physical education and sports science curricula to foster and develop students' cognitive and thinking abilities.